2006
DOI: 10.1142/s0192415x06003588
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Leptin and Beta Endorphin Levels with Weight Loss by Electroacupuncture and Diet Restriction in Obesity Treatment

Abstract: This study aims to investigate the role of changes in leptin and beta endorphin (BE) levels in weight loss following electroacupuncture (EA) application in obesity treatment. EA was applied to 20 females who were 41.45 +/- 4.71 years old and had a body mass index of 36.00 +/- 2.66; and a diet program was applied to 20 females who were 42.30 +/- 4.35 years old and had a body mass index of 34.90 +/- 3.21. There was a 4.5% weight reduction in the patients with EA application, whereas patients on diet restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…In line with these observations, we demonstrated that low-frequency EA decreases mRNA expression of inflammatory markers in mesenteric adipose tissue of rats with DHTinduced PCOS (52). In studies not related to PCOS, daily low-frequency EA treatment for 4 wk in rats and humans reduced food intake and weight (6,37). EA treatment has also been shown to improve lipid profile in mice (41) and humans (7).…”
Section: E556supporting
confidence: 71%
“…In line with these observations, we demonstrated that low-frequency EA decreases mRNA expression of inflammatory markers in mesenteric adipose tissue of rats with DHTinduced PCOS (52). In studies not related to PCOS, daily low-frequency EA treatment for 4 wk in rats and humans reduced food intake and weight (6,37). EA treatment has also been shown to improve lipid profile in mice (41) and humans (7).…”
Section: E556supporting
confidence: 71%
“…Based on previous studies, fasting plasma levels in obese subjects showed that levels of ghrelin, adiponectin, cholecystokinin (CCK), and NPY decreased, while leptin levels increased. 8,20 Unlike the findings in obese individuals, the current authors suggest that the acupoints chosen caused a release in ghrelin during ACU to stimulate appetite, hence increasing hunger in the study's ''overweight'' population. This is different, compared to other studies that showed ACU suppressed appetite by increasing serotonin levels 27 and promoted satiety in the HYP.…”
Section: Discussioncontrasting
confidence: 73%
“…30 Based on Traditional Chinese Medicine (TCM) principles, the combination of ST 36 and SP 9 actually increases the hunger response; hence, this combination would be useful for treating anorexia or patients receiving chemotherapy. ST 36 is supposed to promote satiety, regulate intestinal motility, cause sedation, 8 and increase excitability of the satiety center in the VMH. 31 This acupoint has been reported to increase motility in individuals with hypoactive intestines and vice-versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Who reported that energy restriction resulting in even modest weight loss suppresses endogenous cholesterol synthesis which leads to a decline in circulating lipid concentrations and increased insulin sensitivity that contributes in improving lipoprotein profile after treatment of obesity (19). Electroacupuncture can reduce the body weight by 4.5%, with a parallel reduction in the leptin level, total cholesterol, triglyceride, and LDL cholesterol by increasing the beta-endorphin level which stimulates lipolysis (20). Acupuncture has a good regulation effect on lipid metabolism and plasma cycling adenosine monophosphate (cAMP) that is involved in the activation of phosphorylase helping glycogenolysis and on lipase enzyme helping lipolysis (21).…”
Section: Discussionmentioning
confidence: 99%